Periodontal Health Status of Children with Type 1 Diabetes Mellitus (Annals of Medical Research, 2021)
Aim: Type 1 diabetes mellitus (DM1) is the most common chronic disease in children and adolescents. The purpose of this study was to determine the relationship between Type 1 diabetes mellitus and periodontal health and also the effect of metabolic control level on both periodontal and dental health.
Keywords: Children; Dmft; Periodontal; Type 1 Diabetes.